The Juridical Accountability Analysis Notary against the Entry of Criminal Actions Incorrect Information in the Deed of Inheritance - Anggara, Dedy Yudistian (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The deed of inheritance is included in the party's deed. A notary who makes a party's deed, may not enter incorrect (false) information in the inheritance deed he makes, but the party facing the making of an inheritance deed does not rule out the possibility of providing incorrect (false) information. Case No. 259/Pid.B/2015/PN.Cjris one example of a case where a notary is held criminally responsible for entering incorrect (false) information into an inheritance deed. The question is why in this case only the notary is held accountable. The purpose of this study was to analyze the responsibility of a notary in the crime of entering incorrect information in the deed of inheritance case case study No.259/Pid.B/2015/PN.Cjr and find out the legal consequences of an inheritance deed made by a notary based on incorrect information. This study uses a normative juridical approach with a case approach. The case to be studied is case No. 259/Pid.B/2015/ PN.Cjr. The specifications in this study include analytical descriptive and the type of data used is secondary data, with data collection methods including literature studies and documentation studies which are then analyzed qualitatively. Based on the research results it is known that the responsibility of a notary in the crime of entering incorrect (false) information in the inheritance deed in Case No.259/Pid.B/2015/PN.Cjr is based on Article 263 paragraph (1) of the Criminal Code and on the fulfillmentThe three elements of error in criminal law, namely:a.the ability to be responsibleDefendant, where at the time of making the deed of inheritancefalseThe defendant is in good health; b. hthe Defendant's inner relationship with his actions which were intentional, where the Defendant's intention to make a fake inheritance certificate was as a basis for making a grant deed and giving power of attorney; c.tthere are no things that abolish the punishment for the Defendant, either as justification reasons or excuses. The legal consequences of an inheritance deed made by a notary based on incorrect (fake) information do not necessarily make the inheritance deed null and void. The aggrieved parties must submit a lawsuit to the court to cancel the deed. If based on a court decision it is stated that the inheritance deed is cancelled, then the legal consequences arising from the cancellation of the inheritance deed are:deed of grants and power of attorneymade under the deed of inheritance by itself null and void. Next becausedeed of grants and power of attorneynull and void, then all forms of legal action against the inheritance of the heir, which is based on the grant deed and the granting of power of attorney become invalid and have no legal force.Keywords: Accountability; Fake; Inheritance.